2000
DOI: 10.1182/blood.v96.3.885
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient gene transfer in naive human T cells with a murine leukemia virus-based vector

Abstract: Retroviral vectors based on the Moloney murine leukemia virus (MuLV) have become the primary tool for gene delivery into hematopoietic cells, but clinical trials have been hampered by low transduction efficiencies. Recently, we and others have shown that gene transfer of MuLV-based vectors into T cells can be significantly augmented using a fibronectin-facilitated protocol. Nevertheless, the relative abilities of naive (CD45RA+) and memory (CD45RO+) lymphocyte subsets to be transduced has not been assessed. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Some studies have reported that IL-7 does not alter the phenotype of naïve lymphocytes and has no effect on activation markers. 39,[46][47][48] Others have observed that IL-7 induces the up-regulation of certain activation markers (CD25/CD95) but because these changes were not accompanied by conversion of the cells from CD45RA + to CD45RO + phenotype, these changes were classified as minimal. 40,41 In our study, we included three separate controls (untreated, IL-2-treated, and fresh) with the realization that each has its own limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that IL-7 does not alter the phenotype of naïve lymphocytes and has no effect on activation markers. 39,[46][47][48] Others have observed that IL-7 induces the up-regulation of certain activation markers (CD25/CD95) but because these changes were not accompanied by conversion of the cells from CD45RA + to CD45RO + phenotype, these changes were classified as minimal. 40,41 In our study, we included three separate controls (untreated, IL-2-treated, and fresh) with the realization that each has its own limitations.…”
Section: Discussionmentioning
confidence: 99%
“…studied. Dardalhon et al (2000) used a retroviral vector encoding eGFP and packaged with GALV to transduce mature PBMC and T cells from umbilical cord collections. Naive umbilical cord T cells were shown to switch from CD45RA to the CD45RO phenotype after 6 d of stimulation, and were transduced at lower efficiency than mature T cells.…”
Section: Discussionmentioning
confidence: 99%